2022
DOI: 10.1186/s13023-022-02528-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological consequences of compromised ocular immune privilege accelerate retinal degeneration in retinitis pigmentosa

Abstract: Background Retinitis pigmentosa (RP) is a hereditary retinal disease which leads to visual impairment. The onset and progression of RP has physiological consequences that affects the ocular environment. Some of the key non-genetic factors which hasten the retinal degeneration in RP include oxidative stress, hypoxia and ocular inflammation. In this study, we investigated the status of the ocular immune privilege during retinal degeneration and the effect of ocular immune changes on the periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…In this study, we showed the degree of pigmentation of in vitro cultured iPSC-RPE cells did not project specific gene ontological clusters, although it correlated to some extent with the expressions of functional genes of the RPE, such as complement- and lysosome-related genes. Eye, as well as brain and testis, is an immune privilege organ, where inflammation by the immune system is minimized ( Zhou and Caspi, 2010 ; Chen et al, 2019 ; Mohan et al, 2022 ). To protect the photoreceptors from pathogens in this immune suppressive environment, RPE has an immune cell-like aspect with the capability of complement activation ( Kunchithapautham et al, 2014 ; Chen et al, 2019 ; Jensen et al, 2020 ; Tan et al, 2020 ; Schäfer et al, 2020 ) and phagocytosis ( Boulton, 2014 ; Lehmann et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed the degree of pigmentation of in vitro cultured iPSC-RPE cells did not project specific gene ontological clusters, although it correlated to some extent with the expressions of functional genes of the RPE, such as complement- and lysosome-related genes. Eye, as well as brain and testis, is an immune privilege organ, where inflammation by the immune system is minimized ( Zhou and Caspi, 2010 ; Chen et al, 2019 ; Mohan et al, 2022 ). To protect the photoreceptors from pathogens in this immune suppressive environment, RPE has an immune cell-like aspect with the capability of complement activation ( Kunchithapautham et al, 2014 ; Chen et al, 2019 ; Jensen et al, 2020 ; Tan et al, 2020 ; Schäfer et al, 2020 ) and phagocytosis ( Boulton, 2014 ; Lehmann et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Be that as it may, this peripheral expression is correlated with the induction of the anti-transgene immune response that we describe. Several questions must be further investigated, especially the impact in a pathophysiological context in which the retina and the blood-retinal barrier is degenerated 46 . A leakage at lower doses might occur and could trigger a pro-inflammatory immune response at doses lower than ones we have tested in wild type mice.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed the degree of pigmentation of in vitro cultured iPSC-RPE cells did not project specific gene ontological clusters, although it correlated to some extent with the expressions of complement-and lysosome-related genes. Eye, as well as brain and testis, is an immune privilege organ, where inflammation by the immune system is minimized (Zhou et al 2010;Chen et al 2019;Mohan et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed the degree of pigmentation of in vitro cultured iPSC-RPE cells did not project specific gene ontological clusters, although it correlated to some extent with the expressions of functional genes of the RPE, such as complement- and lysosome-related genes. Eye, as well as brain and testis, is an immune privilege organ, where inflammation by the immune system is minimized (Zhou et al 2010; Chen et al 2019; Mohan et al 2022). To protect the photoreceptors from pathogens at this immune suppressive environment, RPE has an immune cell-like aspect with the capability of complement activation (Kunchithapautham et al, 2014; Chen et al 2019; Jensen et al, 2020; Li et al, 2020; Schäfer et al, 2020) and phagocytosis (Boulton, 2014; Lehmann et al, 2014).…”
Section: Discussionmentioning
confidence: 99%